2021
DOI: 10.52082/jssm.2021.721
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Changes in Strength and Power in Elite Rugby League: A Systematic Review and Meta-Analysis

Abstract: The ability of a rugby league player to express high levels of strength and power is crucial for success in competition. Although researchers have shown relationships between physical attributes and performance, there is a lack of information related to changes in strength and power across various phases of the season. The purpose of this review was to identify the magnitude of change in muscular strength and power during different phases of an elite rugby league season. Percentage change and effect size were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 59 publications
3
12
0
Order By: Relevance
“…Comparing these results with previous research, the mean isometric mid-thigh pull peak force for Australian women’s backs (+369 N) and forwards (+515 N) surpassed the values found for backs and forwards in this study [9]. Maximal strength is a pivotal determinant of successful rugby league performance, correlating with improved technical skill, greater match-play distances covered, enhanced sprint performance, and higher playing standards [37,39]. Hence, prioritising maximal strength development during the pre-season period is crucial, as this phase often yields more noticeable strength improvements compared to the in-season phase [37].…”
Section: Discussionsupporting
confidence: 65%
“…Comparing these results with previous research, the mean isometric mid-thigh pull peak force for Australian women’s backs (+369 N) and forwards (+515 N) surpassed the values found for backs and forwards in this study [9]. Maximal strength is a pivotal determinant of successful rugby league performance, correlating with improved technical skill, greater match-play distances covered, enhanced sprint performance, and higher playing standards [37,39]. Hence, prioritising maximal strength development during the pre-season period is crucial, as this phase often yields more noticeable strength improvements compared to the in-season phase [37].…”
Section: Discussionsupporting
confidence: 65%
“…Taking into account the changes in both tests, it appears that male collegiate golfers show similar seasonal effects to other sports where explosive lower body movements such as the vertical jump task have been maintained or improved while changes in strength appear to be less consistent. [18][19][20] Specifically, concerning strength changes, the current study displays this inconsistency. Peak force was reduced to a nonsignificant level while force at 100, 200, and 300 ms each showed significant reductions.…”
Section: Discussionmentioning
confidence: 56%
“…Findings from this investigation are similar to those seen across other sports with reductions in strength and maintenance of vertical jump abilities. [18][19][20][21] Additionally, this investigation sought to use a single-subject analysis to identify if group means were caused by a large shift from single participants as golf is an individual sport. We found that general trends existed for each variable of interest however, each variable also displayed individuals having opposing changes over the course of the ten weeks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The seasonal nature presents a variety of physical challenges that can cause fluctuations in a player's physical development during the season (22); these include a decrease in resistance training load to allow for increases in the volume of technical and tactical skill training. In addition, muscle damage and inflammation after a match, potentially causing decrements in muscle performance, may be problematic for developing or maintaining muscular strength and power (17,35). Hence, the players' ability to acquire and maintain appropriate body composition and physical characteristics, both preseason and in-season, is of paramount importance.…”
Section: Introductionmentioning
confidence: 99%